Strategi Resolusi Konflik Politik Lokal Berbasis Nilai Komunikasi Nabi di Labuhan Batu Selatan - Silaen, Mulkan Darajat; Nasution, Hasyimsyah; Azhar, Anang Anas (Medan Resource Center, 2025)
This study explores the implementation of prophetic communication values—?idq (honesty), sh?r? (deliberation), ?adl (justice), and ra?mah (compassion)—as a strategic approach to resolving local political conflicts in Labuhan Batu Selatan, North Sumatra. The research examines how these Islamic ethical principles are actualized by political actors, religious leaders, and civil society during the post-election period. Grounded in a qualitative case study design, the study draws on 12 in-depth interviews with key informants, including local government officials, clerics, NGO representatives, and community leaders. It also incorporates document analysis of local media coverage and election-related public statements. The study adopts a constructivist theoretical framework, emphasizing how actors interpret and enact moral-religious values within political discourse. Thematic analysis was employed to identify patterns in ethical and dialogical communication across multiple stakeholder groups. Findings reveal that while individual actors often internalize and express prophetic values in informal settings, formal political communication remains dominated by transactional and polarizing narratives. Religious leaders and civil society organizations serve as moral intermediaries, but their capacity is constrained by the lack of institutional mechanisms for dialogue and reconciliation. This study contributes both theoretically and practically. Theoretically, it offers a moral-ethical lens to the study of local political communication in pluralistic Muslim societies. Practically, it suggests that the integration of prophetic values into political discourse can promote ethical governance and strengthen social cohesion in post-electoral contexts.